IMPLEMENTASI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MELALUI KEGIATAN PEMBERSIHAN DAN PENANAMAN POHON DI PANTAI KOMODO KOTA TEGAL - Prasetya Putra Nugraha; Akhmad Aniq Barlian (ADISAM PUBLISHER, 2024)
This research aims to determine the effectiveness of citizenship Education learning through cleaning and planting trees at Komodo Beach, Tegal City. The research method used a questionnaire distributed to 24 students who were then analysed, so this activity is very effective in learning, but in its implementation there needs to be sustainability so that is has maximum benefit to society. Therefore, it is necessary to have a new curriculum for citizenship Education courses to achieve learning objectives optimally